Energy contributions of competitive freestyle events
The actual contributions of the anaerobic and aerobic energy systems to various racing distances were determined. Summary: 1. Both energy capacities need to be developed fully before embarking on exact specific training in the latter phases of training. 2. A solid aerobic base needs to be established before undertaking any anaerobic training. 3. The aerobic energy requirement is greater than previously thought for all distances. 4. Power is a particularly important characteristic to be developed in 50 and 100 m training. 5. Lactate tolerance training is most important for 200 and 400 m events. 6. Swimmers with larger anaerobic and/or aerobic capacities have the potential to achieve higher performance levels than individuals with lesser capacities.